Intestinal stem cell pool regulation in drosophila - Jin, Yinhua; Patel, Parthive H.; Kohlmaier, Alexander; Pavlović, Bojana; Zhang, Chenge; Edgar, Bruce (Stem cell reports, 2017)
Summary Intestinal epithelial renewal is mediated by intestinal stem cells (ISCs) that exist in a state of neutral drift, wherein individual ISC lineages are regularly lost and born but ISC numbers remain constant. To test whether an active mechanism maintains stem cell pools in the Drosophila midgut, we performed partial ISC depletion. In contrast to the mouse intestine, Drosophila ISCs failed to repopulate the gut after partial depletion. Even when the midgut was challenged to regenerate by infection, ISCs retained normal proportions of asymmetric division and ISC pools did not increase. We discovered, however, that the loss of differentiated midgut enterocytes (ECs) slows when ISC division is suppressed and accelerates when ISC division increases. This plasticity in rates of EC turnover appears to facilitate epithelial homeostasis even after stem cell pools are compromised. Our study identifies unique behaviors of Drosophila midgut cells that maintain epithelial homeostasis.